#### Answer

$x^{4}$

#### Work Step by Step

$\sqrt[3] (x^{12})=x^{4}$, because $(x^{4})^{3}=x^{4}\times x^{4}\times x^{4}=x^{4+4+4}=x^{12}$

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

$x^{4}$

$\sqrt[3] (x^{12})=x^{4}$, because $(x^{4})^{3}=x^{4}\times x^{4}\times x^{4}=x^{4+4+4}=x^{12}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.